E-Wallet (Study on Legal Protection for Fund Users, OVO, Link Aja) - Andria Luhur Prakoso; Nabil Dzaky Nuafal (Universitas Muhammadiyah Surakarta, 2023)
Electronic wallets are still important to support activities in the economic sector, but not only do consumers feel the good impact, but there are also disadvantages for the consumers themselves. This research uses normative methods and collects data through library research and the results of this research inform readers about how to claim compensation caused by the application that is examined and the responsibility of the business actor in providing where and guarantees for consumers who use e-wallet application.